Species composition and toxicity of the genus Pseudo-nitzschia in Taiwan Strait, including P. chiniana sp. nov. and P. qiana sp. nov. - Huang, C.X.; Dong, H.C.; Lundholm, N.; Teng, S.T.; Zheng, G.C.; Tan, Z. (Elsevier B.V., 2019)
In a field survey in the Taiwan Strait during April 2016, the species composition and the domoic acid production of the diatom genus Pseudo-nitzschia were investigated. A total of 80 strains of Pseudo-nitzschia were established, and species identification was determined based on a combination of morphological and molecular data. Fourteen taxa were recognized, i.e., P. americana, P. brasiliana, P. calliantha, P. cuspidata, P. galaxiae, P. lundholmiae, P. multiseries, P. multistriata, P. pseudodelicatissima, P. pungens var. aveirensis, P. pungenus var. pungens and P. sabit, as well as two novel species P. chiniana C.X. Huang & Yang Li and P. qiana C.X. Huang & Yang Li. Morphologically, P. chiniana is characterized by striae comprising one or two rows of poroids, and valve ends that are normally dominated by two rows of poroids within each stria. Whereas P. qiana is unique by having a narrow valve width (1.3–1.5 μm) and sharply pointed valve ends. Both taxa constitute their own monophyletic lineage in the phylogenetic analyses inferred from LSU and ITS2 rDNA, and are well differentiated from other Pseudo-nitzschia species. Pseudo-nitzschia chiniana forms a group with P. abrensis and P. batesiana in LSU and ITS trees, whereas P. qiana is sister to P. lineola. When comparing ITS2 secondary structure, five CBCs and seven HCBCs are recognized between P. chiniana and P. abrensis, and four CBCs and ten HCBCs between P. chiniana and P. batesiana. Two CBCs and eight HCBCs are found between P. qiana with P. lineola. The ability of the strains to produce domoic acid was assessed, including a potential toxin induction by the presence of brine shrimps. Results revealed production of domoic acid in six strains belonging to three species. Without presence of brine shrimps, cellular DA (pDA) was detected in four P. multiseries strains (1.6 ± 0.3, 26.6 ± 2.7, 68.3 ± 4.2 and 56.9 ± 4.7 fg cell−1, separately), one strain of P. pseudodelicatissima (0.8 ± 0.2 fg cell−1) and one strain of P. lundholmiae (2.5 ± 0.4 fg cell−1). In the presence of brine shrimps, pDA contents increased significantly (p < 0.05) in P. lundholmiae (strain MC4218) and P. multiseries (strain MC4177), from 2.5 ± 0.4 to 8.9 ± 0.7 and 1.6 ± 0.3 to 37.2 ± 2.5 fg cell−1 respectively.